5-Hydroxytryptamine-3 receptor antagonist and dexamethasone as prophylaxis for chemotherapy-induced nausea and vomiting during moderately emetic chemotherapy for solid tumors: a multicenter, prospective, observational study - Reiko Matsui; Kenichi Suzuki; Tomomi Takiguchi; Makoto Nishio; Takeshi Koike; Toshinobu Hayashi; Takashi Seto; Yuki Kogure; Naoyuki Nogami; Kimiko Fujiwara; Hiroyasu Kaneda; Tomohiko Harada; et al. (BMC, 2020)
Abstract Background Of patients receiving moderate emetic risk chemotherapy (MEC), 30-90% experience chemotherapy-induced nausea and vomiting (CINV); however, the optimal antiemetic treatment remains controversial. Methods In this multicenter, prospective, observational study of adults treated with MEC while receiving chemotherapy for various cancer types in Japan, the enrolled patients kept diaries documenting CINV. All participants received a 5-hydroxytryptamine-3 receptor antagonist and dexamethasone. Results Of the 400 patients enrolled from May 2013 to January 2015, 386 were eligible for evaluation. The median age was 64 (range, 26-84). The overall complete response (CR; no emetic events and no antiemetic measures) rate was 64%. The proportion of patients showing CR was low in the carboplatin (CBDCA)- and oxaliplatin-based chemotherapy groups, especially among women. We showed that the CR rates in men were high in the CBDCA (AUC5) + etoposide (ETP) (80%), capecitabine plus oxaliplatin (CAPOX) (78%), and CBDCA+ paclitaxel (PTX) groups for lung cancer (73%). Total control (TC; no emetic events, no antiemetic measures, and no nausea) and complete control (CC; no emetic events, no antiemetic measures, and less than mild nausea) were achieved in 51 and 61% of patients, respectively. Logistic regression analysis revealed history of motion sickness, history of pregnancy-associated vomiting and CBDCA-based chemotherapy as risk factors for CR and history of motion sickness and history of pregnancy-associated vomiting as risk factors for TC. Additional, Ages ≥65 years is an independent predictive factor for achieving TC. Conclusions Our data showed that two antiemetics were insufficient to control CINV in patients receiving CBDCA- or oxaliplatin-based chemotherapy. However, two antiemetics may be sufficiently effective for elderly male patients receiving CBDCA (AUC5) + ETP, CBDCA+PTX for lung cancer, or CAPOX. Additionally, we consider that three antiemetics are necessary for women with colorectal cancer receiving CAPOX. Risk factor analysis related to CR showed that CINV prophylaxis in patients treated with CBDCA-based chemotherapy was generally supportive of the guideline-recommended three antiemetics. However, the control of nausea in patients receiving non-CBDCA-based chemotherapy is a key point to note. The further individualization of antiemetic regimens for patients receiving MEC based on both types of chemotherapy regimens and sex is needed.